PERDAGANGAN DALAM ISLAM - Windari Windari (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2015)
Goals to be achieved in this journal to analyze trade in the light ofIslamic moral values, where in the market there are two actors sipenjualand sipembeli. The main source of this journal is the study of literature.Author Taking conclusions There are some things in the trade that doesnot conform to the Islamic shariah. Therefore, there needs to beimprovement of systems and cooperation between all elements ofbusiness, community and government. In the Islamic value determination(determining) the price is not allowed, because the pricing is done bymarket forces, ie the power demand and power supply. This is inaccordance with Islamic trade krateristik where market participantsshould promote piety, fairness and kindness, keeping the symbols ofIslam, applying managerial good.